Estudio de factibilidad para la implementación de un sistema de gamificación enfocado al adulto mayor en Babahoyo - Lema Gomez, Byron Adrian (2021)
In this case study, a brief feasibility analysis is presented to determine the acceptance of creating a gamification system focused on the elderly using playful games that help to improve the various cognitive disabilities that occur in the elderly, the Gamification with the help of technological tools serves as a strategy for recovery and at the same time learning in people thanks to cognitive stimulation that carries a number of benefits for mental improvement. The gamification technique is emphasized because it is an important means of activating curiosity, attracting attention, regenerating memory, as well as providing help through people's learning. The main objective with this case study is to provide an innovative idea for the Ecuadorian population in addition to including the participation and motivation of older adults because today this population has been technologically marginalized for this reason, we proceeded with this feasibility analysis.